TINGKAT PENGETAHUAN REMAJA MENGENAI KANKER SERVIKS DI DUA SEKOLAH DI KABUPATEN GIANYAR, BALI - I Komang Darma Wijaya; I Nyoman Gede Budiana; Ida Bagus Gede Fajar Manuaba; Endang Sri Widiyanti (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2024)
ABSTRACT Cervical cancer become the second highest cancer case in Indonesia which attacks women with a mortality rate of up to 50%. The prevalence of this case has increased in recent years. This cancer, which is caused by infection with the HPV virus, can infect women from the age of 20 until the women is not in their reproductive age. The aim of this study was to determine the level of knowledge of adolescents regarding cervical cancer in two schools in Gianyar Regency. This research is descriptive study with a stratified random sampling method. The data collection method used was by giving questionnaires to students attending SMP Negeri 1 Gianyar and SMA Negeri 1 Gianyar. The questionnaire used consists of 2 aspects, namely knowledge of cervical cancer and knowledge of how to prevent cervical cancer. From this research, 209 respondents were obtained from the two schools, there are 30.14% had a good level of knowledge, 60.29% had a fairly good level of knowledge, and 9.57% had a poor level of knowledge.